Linking R&D Spillovers to Market Structure and Its Impact on Equilibrium Results - Alghamdi, Mohamad (Communications in Mathematics and Applications, 2020)
We develop an R&D network model by linking R&D spillovers to the degree of substitution of goods. Then, we examine the impact of the new model on the equilibrium outcomes under Cournot competition. The results show that the importance of the spillover restriction appears if the substitution degree of goods is small where in this case, the outcomes are maximized under the restricted spillover. The results also show that as the degree of replacement increases, the structure of socially optimal cooperation under restricted spillover effects is more intense than in the case of free spillover effects.